ADHESIVE BEHAVIOR OF POLYCAPROLACTONE/HYDROXYAPATITE COATINGS ON 316L STAINLESS STEEL: A DESIGN OF EXPERIMENTS APPROACH - Agung Prabowo; Ahmad Fadli; Heni Sugesti; Muh Irwan; Syarifuddin Oko; Gading Bagus Mahardika; Marlinda (Program Studi Kimia, Fakultas MIPA, Universitas PGRI Banyuwangi, 2025)
Enhancing the adhesive strength of bioactive coatings is crucial for improving the mechanical stability of metallic implants. This study investigates the effects of three processing parameters—sonication temperature (X₁), PCL/HA ratio (X₂), and drying time (X₃)—on the adhesive strength of poly(ε-caprolactone)/hydroxyapatite (PCL/HA) composite coatings applied to 316L stainless steel substrates. A full factorial 23 experimental design was employed, and the results were analyzed using analysis of variance (ANOVA) and regression modeling. The adhesive strength response ranged from 19.62 MPa to 63.27 MPa. Among the factors studied, the PCL/HA ratio had the most significant positive effect, while drying time showed a minor influence. Interaction plots and response surface analyses revealed a synergistic effect between sonication temperature and PCL/HA ratio, contributing to improved bonding at the coating-substrate interface. The optimization results yielded a predicted maximum adhesive strength of 25.76 MPa at a desirability score of 0.03, highlighting the complexity of parameter interactions. These findings underscore the importance of processing conditions in tailoring coating performance for biomedical applications.